(untitled) (Revista Contexto & Saúde, 2026)
The objective of the present study was to evaluate the association between sociodemographic, obstetric, anthropometric factors, and body image with intuitive eating in pregnant women. This cross-sectional study was conducted between June 2019 and February 2020 with pregnant women receiving care in the public and private healthcare networks in Lavras, Minas Gerais. Sociodemographic, obstetric, and anthropometric data were collected through a semi-structured questionnaire based on national surveys. Body image perception was assessed using the Body Shape Questionnaire, while intuitive eating was measured through the Intuitive Eating Scale. Univariate and multivariate logistic regression analyses were applied, adjusting for sociodemographic, anthropometric, and body image variables. The sample consisted of 189 pregnant women. In the adjusted analysis, it was found that pregnant women who identified as non-white were 3.72 times more likely (95% CI 1.74-8.38) to engage in intuitive eating compared to white women. Additionally, those receiving care in the public sector were 0.25 times less likely (95% CI 0.10-0.56) to practice intuitive eating compared to those assisted in the private sector. These findings suggest that external factors influence intuitive eating at different levels, affecting the perception of physical hunger and satiety cues.